Structural and magnetic properties of mechanochemically synthesized nanocrystalline titanium monoxide - Barudžija Tanja (Hemijska Industrija, 2012)
Nano-sized titanium monoxide (TiO) powder was prepared by mechanochemical synthesis. A mixture of commercial Ti and TiO2 (rutile) powders with the molar ratio of 1:1 was milled in a planetary ball mill for 5, 10, 20, 30 and 60 min under argon atmosphere. The final single-phase titanium monoxide sample was characterized by X-ray diffraction (XRD), magnetic measurements using a superconducting quantum interference device magnetometer (SQUID) and thermogravimetric analysis (TGA). The temperature dependency of the magnetic susceptibility is characterized by significant contribution of Pauli paramagnetism due to conduction electrons.